An ESR spectroscopy study of NaY zeolite supercages UV irradiated in hydrogen - 602127 Abdul Rahim Yacob; Yeoh, Kar Kheng; International Conference on Advancement in Science and Technology (2003 : Kuala Lumpur) (Skudai : Universiti Teknologi Malaysia, 2003)
42